A modified G criterion considering T-stress and differentiating the separation and shear failure in crack propagation. (1st February 2022) - Shen, Zhen; Yu, Hongjun; Guo, Licheng; Hao, Liulei; Huang, Kai
Abstract: In view of shear failure controlled by distortion and separation failure governed by dilation having different significance for the crack propagation, the traditional G criterion is modified by differentiating the volumetric and distortional parts in energy release rates which involve the influence of T-stress. The critical volumetric to distortional energy release rate ratio is introduced as an intrinsic material property. As the critical volumetric to distortional energy release rate ratio increases, the failure pattern for mode II crack gradually transits from separation dominant failure to shear dominant failure. The modified G criterion is theoretically investigated through discussing the influence of critical volumetric to distortional energy release rate ratio, T-stress and fracture process zone size on the crack propagation behavior (i.e., crack kinking angle and fracture resistances). The crack kinking angle is found to reduce as the critical volumetric to distortional energy release rate ratio increases, but enlarge as the T-stress or fracture process zone size increases. The fracture resistances are found to decrease as the critical volumetric to distortional energy release rate ratio, T-stress or fracture process zone size increases. The modified G criterion shows a superior predictability for the experimental results reported by Aliha et al. (2012, 2013), Williams and Ewing (1972) and Mousavi et al. (2020) over the maximum tensile stress criterion (MTS criterion) and traditional G criterion. The modified G criterion has the potential to predict the crack propagation behavior for a variety of materials.